The Morphological Change Of The Word Istihalah - Iqbal Hamdan; Lily Hanefarezan Asbulah; Hakim Nabila Zainal (Ijaz Arabi Journal of Arabic Learning, 2026)
This study seeks to examine the concept of istiḥālah (transformation) as a multidisciplinary concept that integrates Arabic linguistics and Islamic jurisprudence (Fiqh). This concept is generally considered a legal sublety that seeks to purify substances, but this study establishes that istiḥālah is in reality, rooted in the very foundations of Arabic linguistics, based on the triliteral root ḥ-w-l (ح–و–ل), which means transition or change. The study is also based on the application of the istafʿala (استفعل) pattern, which is not limited to "requesting" (ṭalabbut also includes other forms of transformation (taḥawwul),enhancement, intensification, and resultative states (mutāwaʿa). The study also discusses the application of this concept in Islamic jurisprudence, where the debate between "complete" (tāmmah) and "incomplete" (fāsidah) transformation is addressed in modern food science. The study also discusses the flexible application of this concept in Ḥanafī law, where the disappearance of a substance's original essence is required, Unlike the rigid rule of Shafi'i that demands spontaneous and absolute metamorphosis, the study emphasizes the significance of linguistic interpretation in establishing the Halal status of vinegar, gelatin, and food additives such as E471. In conclusion, it appears that the level of metamorphosis is the ultimate determinant of Halal integrity in contemporary times.